Pengaruh Work Family Conflict terhadap Komitmen Organisasi pada Single Mother di Kota Bandung - Alya Nur Nisrina Suhendar; Anna Rozana (Bandung Conference Series: Psychology Science, 2024)
Abstract. In a globalized organizational world with high levels of competition, it cannot be denied that companies need employees who are qualified and committed to the company (Rini & Indrawati, 2019). Organizational commitment is a behavioral dimension to evaluate the continuity of employee commitment in the organization and the possibility of employees to survive and remain members of the organization. This is seen from three aspects: identification, involvement and loyalty as explained by Mowday et al., 1982. Factors involved which has the potential to influence organizational commitment is work family conflict. Work family conflict is a conflict between roles (interrole conflict) where demands in the work domain and the family domain clash with each other (Greenhaus & Beutell 1985). This research aims to determine the effect of work family conflict on organizational commitment among single mothers in the city of Bandung. This research is a non-experimental research that uses the causality method, involving 100 single mothers in the city of Bandung. Purposive sampling technique was used in this research as a sampling technique. Multiple linear regression was used to analyze the data in this study. The result is an R Square value = 0.287 with a sig value of 0.000 < 0.05. It can be interpreted that work family conflict has an effect of 28.7% on single mother organizational commitment in the city of Bandung. Abstrak. Dalam dunia organisasi yang mengglobal dengan tingginya tingkat persaingan, tidak dapat dipungkiri bahwa perusahaan membutuhkan karyawan yang berkualitas dan berkomitmen terhadap perusahaan (Rini & Indrawati, 2019). Komitmen organisasi merupakan dimensi perilaku untuk mengevaluasi kelangsungan komitmen karyawan dalam organisasi dan kemungkinan karyawan untuk bertahan dan tetap menjadi bagian dari anggota organisasi, hal ini dilihat dari tiga aspek: identifikasi, keterlibatan dan loyalitas seperti yang dijelaskan oleh Mowday et al., 1982. Faktor yang berpotensi memberikan pengaruh kepada komitmen organisasi adalah Work family conflict. Work family conflict merupakan konflik antar peran (interrole conflict) di mana tuntutan pada domain pekerjaan dan domain keluarga saling berbenturan (Greenhaus & Beutell 1985). Dalam penelitian ini bertujuan untuk mengetahui pengaruh work family conflict terhadap komitmen organisasi pada single mother di Kota Bandung. Penelitian ini merupakan penelitian non-eksperimental yang menggunakan metode kausalitas, dengan melibatkan 100 single mother di Kota Bandung. Teknik purposive sampling digunakan dalam penelitian ini sebagai teknik untuk pengambilan sampel. Regresi linier berganda digunakan untuk menganalisis data pada penelitian ini. Hasilnya nilai R Square = 0.287 dengan nilai sig 0,000 < 0,05. Dapat diartikan work family conflict berpengaruh sebesar 28,7% terhadap komitmen organisasi single mother di Kota Bandung.